Effects of Temperature and Water Availability on Northern European Boreal Forests - Ruiz-Pérez, Guiomar; Vico, Giulia (Frontiers in Forests and Global Change, 2020)
Boreal forests are warming faster than the rest of the planet. Do the benefits of higher temperatures and longer growing seasons for forest productivity exceed the negative effects of more frequent dry spells and heat waves, shifting precipitation patterns, and higher evaporative demands? And are the effects uniformly distributed geographically? To answer to these questions, the relationship between climatic variables and NDVI—a proxy of forest productivity at regional scale—was explored via Partial Least Square (PLS) regression analyses. We focused on Northern Europe, where contrasting findings on the effects of warming have been reported and that has so far been overlooked by systematic large-scale explorations of the linkages between boreal forest productivity and climatic conditions. The results show that the effects of warmer temperatures on boreal forest productivity are not uniformly positive and that water stress is already negatively affecting these forests. Indeed, increased temperatures appear beneficial in northern and wetter regions, while warmer temperatures mostly reduce forest productivity in southern and drier areas. These results are suggestive of already existing limitations due to water availability and warm temperatures, even in mesic regions like Northern Europe. These conditions are expected to become more frequent and intense in the future, potentially reducing the ability of boreal forests to provide their essential ecosystem services unless forest management practices are adapted to the new conditions.